Pelatihan Penerapan Standar K3 untuk Meningkatkan Keamanan dan Kesehatan Kerja pada UMKM Pengelasan di Desa Kampar - Adi Febrianton; Purnama Irwan; Romiyadi, Romiyadi; Indah Purnama Putri; Yudi Dwianda; Widya Sinta Mustika (Politeknik Kampar, 2025)
Occupational safety and health (K3) is very important to be applied in small and medium industries. In addition to reducing the risk of work accidents, the implementation of K3 can also provide benefits for the industry, such as increasing productivity, maintaining the quality of work results, and creating a safe and comfortable work environment. Kampar Village, Kampa District, has five MSMEs engaged in welding. Based on the survey, almost all of these MSMEs have not implemented the implementation of K3 properly, especially due to the lack of employee awareness in implementing safe work behavior. The lack of employee knowledge about the principles of K3 is also the cause of low concern for occupational safety. In addition, MSMEs have not provided complete personal protective equipment (PPE), so the risk of work accidents is higher. Therefore, training related to the implementation of K3 standards is needed to improve employee welfare while supporting the progress of MSMEs. This training is given to MSME owners in Kampar Village, Kampa District, so that they are able to implement K3 standards consistently and sustainably in welding business activities.